Reduksi Kadar Phospat Limbah Cair Rumah Sakit Menggunakan Bakung Putih (Crinum asiaticum Linn.) (Studi Kasus: RSUD dr. Soehadi Prijonegoro Kabupaten Sragen) - Bayu Kusuma Adi; Elvis Umbu Lolo; Richardus Indra Gunawan; Yonathan Suryo Pambudi (Jurnal Serambi Engineering, 2021)
RSUD dr. Soehadi Prijonegoro Sragen produces liquid waste containing microorganisms, toxic and radioactive chemicals. The results of the laboratory examination showed that the liquid waste level always exceeded the quality standard, namely the parameter of phosphate. The phosphate level in September 2013 was 4.80 mg / L, while in December 2013 the concentration was 2.60 mg / L, so  additional  treatment is needed, one of which is phytoremediation using white daffodils (Crinum asiaticum Linn.). This research method is an experimental research design with  pre-post Test with Control Group Design where the wastewater will pass through a wet tank   containing white lily plants with a residence time of 24 hours/day and a treatment rate  of 1100 liters/day. Th research aimed to determine the effect of phytoremediation of white daffodils on the reduction of phosphate levels and the average percentage of its reduction. The results of this study in the ninth and tenth sample collection  met the quality standards of  1.99 mg / L and 1.89 mg / L. Phytoremediation of white daffodils (Crinum asiaticum linn.) may reduce phosphate levels by 45.59%.